Comparative Study of Islamic and International Humanitarian Law - Nabiebu, Miebaka (NAJAHA, 2023)
The human community has always been characterized by conflict, governed by ethical and legal standards that have evolved with human civilization. This widely accepted standard was eventually defined as contemporary International Humanitarian Law (IHL). This study aims to analyze from two legal perspectives: Islamic and international humanitarian law. The method used in this research is comparative, including qualitative analysis. The results of this study suggest that regulation has developed mainly due to modern European activities, diminishing the potential contributions of other cultural and ethical traditions to its development and codification. However, it should be noted that the principles jus ad bellum (laws governing the use of force) and jus in Bello (the content of the laws of war) are evident in Islamic literature centuries before modern international law was codified, with little attention paid to them. This paper argues that Islamic humanitarian law, which regulates the treatment of prisoners of war, is comprehensive and comparable to the provisions of the 1949 Geneva Convention. In addition, the concept of Siyar's Islamic literature is very similar to the Geneva Conventions. This research augments international relations by examining the degree of concordance between the requirements of Islamic Humanitarian Law and Modern IHL concerning issues of immediate practical relevance in an era when several regions of the world are experiencing armed conflict.